Partisipasi Mahasiswa KKN dalam Penyusunan Data Pemetaan Jalan sebagai Upaya Pembangunan Berkelanjutan di Kampung Kelam Pagi - Sigit Maryanto; Leo Anaris Sakti; Agung Dewana Firda; Andri Joshua Damian; Elvia Putri Ayu Anggraini; Fadia Anisa; Indah Dwi Lestari; Nadia Ardiyanti; Nikmatul Maula; Reza Ariyanto; Rihadatul Aisy; Dios Sarkity (Jurnal Pengabdian Masyarakat Waradin, 2025)
Kampung Kelam Pagi, Dompak Village, focused on mapping the local road network as a foundation for sustainable development planning. The data collection process combined observation, interviews, and digital recording, resulting in both technical data (such as road length, width, and condition) and social data (including road naming conventions and patterns of community usage). The findings indicate notable disparities in infrastructure quality, with main roads mostly paved, while smaller neighborhood roads remain unpaved and lack adequate street lighting. This disparity in infrastructure quality highlights the need for targeted interventions to address the basic infrastructure needs of the community. In addition, the study emphasizes the importance of community involvement in the mapping process, which not only strengthened the social value of the maps but also fostered collective awareness of the importance of spatial data in village development. The discussion further underscores that local data availability is crucial for more participatory, inclusive, and community-oriented village planning, where decisions are based on accurate, locally sourced information. This study demonstrates that KKN activities do more than just provide technical data; they also help reinforce social capacity, empowering local communities to actively contribute to sustainable development efforts. Ultimately, such initiatives contribute to creating more resilient and well-informed communities that can participate in and benefit from development planning.